The war in Ukraine exposes supply tensions on global agricultural markets: Openness to global trade is needed to cope with the crisis - Thomas Glauben; Miranda Svanidze; Linde Johanna Götz; Sören Prehn; Tinoush Jamali Jaghdani; Ivan Djuric; Lena Kuhn (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2022)
The war in Ukraine has aggravated existing tensions on the agricultural commodities market. Since late 2021, prices for commodities such as grains and vegetable oils have reached record highs, surpassing even the levels of the global food price crises of more than a decade ago. Now, the invasion of Russian forces in Ukraine has sent prices soaring even higher. This has above all affected import-dependent countries in the MENA region and sub-Saharan Africa, which rely heavily on Russian and Ukrainian wheat. Disruptions to exports from the Black Sea region and high prices are further destabilizing food security in these regions. However, global demand for wheat is expected to be met in the current marketing year since countries such as Australia, India and the USA will increase exports to fill the gap left by Russia and Ukraine. It is difficult to predict what will happen beyond this marketing year, as this will be determined by the development of the current conflict in addition to agricultural fundamentals in key supply and demand regions. Global food systems and competitive international trade structures, in particular, are key to dealing with crises and mitigating the risks of food shortages. That way, disruptions in some exporting regions can be compensated for by exports from another. However, this requires greater collaboration in international trade. Any calls to move towards a centrally planned economy or autarky are strongly advised against, as this would only be to the detriment of food security in the Global South. – – Der Krieg in der Ukraine hat die seit zwei Jahren bestehende angespannte Versorgungslage auf den internationalen Agrarrohstoffmärkten nochmals verstärkt. Die Preise für Agrarrohstoffe, wie Getreide und Pflanzenöle, übersteigen schon seit Herbst 2021 die Hochpreisniveaus der Nahrungskrisen vor gut einem Jahrzehnt und haben mit Einmarsch russischer Truppen in die Ukraine nochmals angezogen. Besonders betroffen sind die nachfrageboomenden Weizenimporteure in der MENA-Region und in Afrika südlich der Sahara. Russland und die Ukraine sind deren Hauptlieferanten. Lieferengpässe aus der Schwarzmeerregion, gepaart mit hohen Preisen, belasten die ohnehin kritische Ernährungssituation in diesen Regionen zusätzlich. Dennoch, nach gegenwärtigem Stand können die Weizenmärkte im laufenden Wirtschaftsjahr bedient werden. Zusätzliche Exporte aus anderen Regionen, darunter Indien, den USA, und Australien, werden die geringeren Liefermengen aus Russland und vor allem der Ukraine im Rest der laufenden Saison weitgehend ausgleichen. Die Entwicklungen für das nächste Wirtschaftsjahr und darüber hinaus sind hingegen schwer vorauszusehen. Neben der Entwicklung des Konfliktes und dessen Folgen hängen sie natürlich weiterhin von den gängigen agronomischen Fundamentalfaktoren in zentralen Angebots- und Nachfrageregionen ab. In solchen Knappheitssituationen zeigt sich, dass eine global agierende Nahrungswirtschaft und insbesondere wettbewerblich organisierte internationale Handelsstrukturen geeignet sind, Krisen und Risiken zu begegnen. Lieferausfälle aus bestimmten Regionen lassen sich durch Lieferungen anderer Regionen kompensieren. Entsprechend kann nur ein Mehr an internationaler Vernetzung gefordert werden. Vor Rufen nach planwirtschaftlichen Transformationen oder gar Autarkie muss eindringlich gewarnt werden. Alles dies würde zu Lasten hungernder Menschen im globalen Süden gehen.
urn:nbn:de:gbv:3:2-880459
Keywords: 330; Krieg; Getreide; Agraraußenhandel; Lieferkette; International; Ukraine; Russland; MENA-Staaten; Subsahara-Afrika